Harapan, Regulasi Emosi dan Kepuasan Hidup Pasien yang Baru Didiagnosis Kanker: Studi Pendahuluan - Sandra Handayani Sutanto; Pradipta Christy Pratiwi; Christiany Suwartono; Trisya Christine Mayong (Jurnal Ilmiah Psikologi MIND SET, 2021)
Currently, cancer is one of the main causes of death in the world, while cancer prevalence in Indonesia has increased every year. Unfortunately, cancer is not an easily detected disease and it often causes initial shock when the patients first received the diagnosis. These patients are confronted with feelings of uncertainty and threat about their lives, and it can cause inevitable stress to the individuals, which will affect the healing process. This study aims to explore some variables in psychology such as hope, emotion regulation, and satisfaction with life. The research method used is descriptive quantitative, purposive sampling and the number of subjects is 11 people. The results showed a tendency for high levels of hope, low to moderate levels of life satisfaction, emotional regulation using cognitive appraisal and suppression of expression in patients who had just been diagnosed with cancer. It is expected that the description of the data in these variables can be used in a preliminary study for further research so that these variables can play a role in helping newly diagnosed patients who are undergoing treatments or in the healing process.